(untitled) (مجلة الواحات للبحوث والدراسات, 2026)
The growth of Internet use is one of the most distinctive features of the globalization era we live in, whether in terms of the number of emails exchanged, the number of web pages available on the network, the number of users, or the various commercial activities connected to the Internet such as e-commerce and related contract formation. These developments have raised very important and complex legal issues, as current laws have become insufficient for application in the Internet environment, especially due to the increasing disputes, particularly in e-commerce contracts. Among the methods to resolve these disputes, electronic arbitration has emerged as a modern approach to settle them, responding to the specific characteristics of the electronic environment.